Analisis Anteseden Niat Pembelian Ulang Ponsel Pintar - Regy Citra Perdana; Ratna Sari; Dedi Hartawan (JEMBATAN, 2020)
Smartphones, with all of their features, are now becoming a lifestyle and needs for the users. The users tend to replace their smartphones for many reasons. This makes some users feel dissatisfied just by using smartphones of the same brand, both for technical or lifestyle aspects. Smartphone producers are supposed to maintain the users to use the same brands but they sometimes don't understand the real factors that push the consumers to keep using the same brand. This create a gap for research in analyzing consumers' repurchasing intention in replacing their smartphones. This research is conducted in Indonesia using online survey and questionnaire with taking sampling quota from Java and Sumatera with a total of 190 respondents. The research method is partial testing with simple regression and multiple regression then continued with path analysis to see corellation between variables. In this research it can be concluded that based on the construct of expectations confirmation theory model (ECM) that all variables such as confirmation of expectations, brand attachment, perceived benefits, and satisfaction have a positive and significant effect on repurchase intention. So that by testing this theory smartphone manufacturers are expected to pay more attention to the right marketing strategies to continue to maintain or get new consumers to continue to buy smartphones.